Coastal Catastrophe: Coastal Shrimp Farms under Siege by Jellyfish - A Study from Maharashtra Coast of India - Shree, Naga Kalpitha N. N.; Mano, Ashpel M. R.; Iburahim, Abuthagir S.; Landge, Asha T.; Nayak, B. B.; Ramkumar, S.; Ramteke, Karankumar; Kumawat, Tarachand; Lakshmanan, Ranjith; Saravanan, Raju (International Journal of Bio-resource and Stress Management, 2025)
This study was conducted from October, 2022 to July, 2023, in shrimp culture ponds in northern Maharashtra, India, examined the dynamics of these organisms in aquaculture systems. It investigated the emergence and ecological impacts of gelatinous zooplankton in shrimp culture ponds along the northern Maharashtra coast of India. Aquaculture, recognized as the fastest-growing global food-producing sector, was increasingly threatened by the proliferation of gelatinous zooplankton, particularly jellyfish species, in coastal ecosystems. Field investigations in Penaeus (Litopenaeus) vannamei shrimp ponds revealed a noticeable rise in the populations of Tripedalia cystophora (mangrove box jellyfish), Blackfordia sp., Turritopsis sp. (immortal jellyfish), and the ctenophore Pleurobrachia pileus (sea gooseberry). These blooms led to severe disruptions in shrimp growth and survival due to competition for feed and oxygen, and direct physical damage to post-larvae caused by nematocyst stings. The study identified inlet channels connected to coastal waters as a major route for zooplankton intrusion into culture systems. Satellite-derived environmental data showed a positive correlation between sea surface temperature (SST), chlorophyll-a concentrations, and the occurrence of gelatinous zooplankton. Laboratory trials tested mitigation strategies, with tea seed cake (2.5 ppm) demonstrating effectiveness in eradicating jellyfish and ctenophores without negatively impacting shrimp larger than 1 g. This research highlighted the growing threat of gelatinous organisms in aquaculture and underscores the urgent need for continued monitoring, improved water management, and targeted control measures. Strategic adaptation was critical in response to climate-driven changes, especially rising SSTs and eutrophication, along India's vulnerable coastal aquaculture zones.